Interrupções e distrações na assistência de enfermagem na Unidade de Terapia Intensiva-COVID-19 em um hospital universitário - Fonseca, Renata Elizabete Pagotti da (2022)
Frequent disruptions, whether from interruptions or distractions, negatively impact health care, impairing the cognitive process. When a task is interrupted, when resuming, the professional needs time to return to the point where he stopped, and it is possible that some steps of the process are omitted or repeated and, consequently, can lead to errors. In view of this theme, we chose to study interruptions and distractions during the activities carried out by the nursing team in an ICU for the care of patients with COVID-19 and reflect on strategies to reduce these interruptions and distractions. The objective of was to analyze the interruptions and distractions witnessed by nurses and nursing technicians, as well as the perception of these professionals on this topic. The development of the research took place in three phases. In phase I, a literature review was carried out, to list the main interruptions and distractions experienced by the nursing team in the literature and the strategies to minimize them. In phase II, on-site observations were carried out and in phase III, the interview with the nursing team was carried out. The theoretical framework used was patient safety. Data analysis in phase I was performed with a structured instrument, in phase II it was performed through absolute and percentage frequencies and through measures such as mean, standard deviation, minimum, median and maximum, Poisson regression model and regression model Gamma. For all analyses, a significance level of 5% was adopted. Finally, in phase III, the analysis took place through Bardin's content analysis. As a result, of the 243 activities performed by the team, 61 of them suffered interruptions (25.1%) and 8 of them suffered distractions (3.29%). The most interrupted activities were the administrative ones, such as annotation in the electronic system, printing of labels for the collection of exams and in carrying out the systematization of nursing care. However, it was observed that there were interruptions in care activities, such as when a new patient was admitted to hospital, when checking the prescription and in the preparation and administration of medication. The main source of interruption identified was the nursing technician, followed by equipment, self-interruption and the nurse. There were activities performed by the nursing team that interrupted other collaborators, such as, for example, pronation and supination, intercurrences during the shift and attire, as well as activities performed by the nursing team that were interrupted, such as taking notes. As distractions, cell phone use, parallel conversations and equipment alarms were signaled. It is concluded that interruptions can lead to consequences such as errors in medication preparation and administration, stress, delay and physical and emotional overload, and strategies to avoid interruptions and distractions in the work environment are considered important. This study was innovative in carrying out observations within an ICU for the care of patients with COVID-19, to collect data on interruptions and distractions to reflect on strategies to ensure that work is carried out safely.